2011
DOI: 10.1111/j.1365-2761.2011.01245.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Flavobacterium psychrophilum in fish serum correlates with pathogenicity

Abstract: Flavobacterium psychrophilum isolates, obtained from ayu, Plecoglossus altivelis, three species of salmonids and two species of cyprinids in Japan, were used in this study. Bacteria were inoculated to serum prepared from ayu or red spotted masu trout (RSMT), Oncorhynchus masou ishikawae, and incubated at 18 °C for 24 h. All isolates (n = 19) from ayu grew well with a 9- to 116-fold increase of CFU in ayu serum, while CFU decreased markedly in RSMT serum. In contrast, isolates (n = 17) from fish species other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Institutions that provided these isolates and previous publications on these isolates are listed [11,14,16,44-47]. …”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Institutions that provided these isolates and previous publications on these isolates are listed [11,14,16,44-47]. …”
Section: Supplementary Materialsmentioning
confidence: 99%
“…However, F. psychrophilum infections have been reported in a wide range of both anadromous and non-anadromous salmonids of various sizes [34][35][36][37][38][39][40][41][42]. In addition, F. psychrophilum has either caused disease or been detected in Japanese eel Anguilla japonica [43], European eel Anguilla anguilla [44], common carp Cyrpinus carpio [44], crucian carp Carassius carassius [44], tench Tinca tinca [44], ayu Plecoglossus altivelis [27,29], pale chub Zaco platypus [28], perch Perca fluviatilis [45], and roach Rutilis rutilis [45].…”
Section: Epidemiologymentioning
confidence: 99%
“…There are also a number of distinct genetic lineages, with the number appearing to increase with the refinement of molecular DNA techniques [19,20,40,79] with considerable genetic variation and variation in virulence among strains [19,25,45,80,81]. Strain virulence may also be fish species specific [42]. Based on RAPD (Random Amplification of Polymorphic DNA) results, Chakroun et al [83] suggested that North America was the source of F. psychrophilum in Asia, and a separate strain from Europe was transferred to Australia and then back to Europe.…”
Section: Pathogenesismentioning
confidence: 99%
“…In addition, molecular analysis of the population structure of this bacterium suggests that there are a number of distinct lineages [ 7 ]. It has been speculated that some strains are species specific [ 9 ] while others are location specific [ 10 ]. Some strains have also been observed to cause only either BCWD or RTFS [ 7 ].…”
Section: Introductionmentioning
confidence: 99%